(untitled) (Itinera, 2023)
Man has often written about the creation of the monster. The monstrous figure frequently appears in a way that differentiates itself from the human by its grotesqueness, its potential immortality, and/or, of course, its desire to defile the body of the human (i.e. zombies, vampires, etc.) This trauma–i.e. that of being other than human–is often categorized as wicked and wrong. In the case of Attack on Titan, there is a deviation from the norm–namely, instead of being seen as merely evil, these monsters are seen as some“one” to sympathize with. Attack on Titan forces us to question the blurry line that is used to divide monster from human,and forces the viewer to question the human condition of the demonized and repressed everyday "monsters." It is our claim that Dina Fritz works as a representation of “monster.” We look at Dina as an example of representative trauma inflicted through horrific events–such as a genocidal war, dehumanization, and, of course, forced bodily violation–and how these traumas create the beasts that lead to such events; i.e. making these “monst[hers]” out of humans. We argue that the characterization of Dina Fritz is a warning to its audience that segregation, violence, and the loss of bodily autonomy perpetuates a cycle of monstrous births/creation. In this article, we will speak not only to the end result of the monstrous creation–i.e. the monst[her]–but also to the line that has been blurred with this monstrous other and the human in the world of Attack on Titan.